Keterampilan Dasar Mengajar Guru dalam Menyediakan Media Pembelajaran AUD - Fauziah Nasution; Wildani Wildani; Fitra Handayani; Rahma Yani; Anti Pebriani Syahpitri (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Education is one important aspect in the development of a country. The teacher as a teacher has a very vital role in creating an effective and enjoyable learning environment for students. One of the factors that can increase the effectiveness of learning is the use of appropriate learning media. Good learning media can help teachers convey learning material more clearly, interestingly, and easily understood by students. This research is qualitative in nature, where we do not collect primary data through surveys or interviews. Keywords: Teaching skills, AUD learning media, Teachers